A Randomized Controlled Trial On The Efficacy Of Two Types Of Manual Toothbrushes In Patients With Fixed Appliances - Zurairah Ibrahim; Azrul Hafiz Abdul Aziz; Ainuddin Yushar Yusof; Diana Md Zahid; Syiral Mastura Abdullah; Rohaya Megat Abdul Wahab (Ectodermal Dysplasia Group-Turkey, 2024)
(J Int Dent Med Res 2019; 12(4): 1533-1539